Political ethics in Indonesia: A study of political ethics of digital citizenship in the 2024 election - Arditama, Erisandi; Lestari, Puji; Munandar, Moh. Aris (Universitas Negeri Semarang, 2024)
This article focused on examining the political ethics of digital citizenship in Indonesia in the digital era at a time of technological and scientific progress, specifically in the context of the 2024 election. Changes supported by advances in information technology have also shaped the political character of each individual in the digital era. There are many negative as well as positive things that arise, making it an interesting discourse to research. This descriptive qualitative research explored data through in-depth interviews and reviewing literature sourced from books and articles and analyzed the content and conversations of digital citizens on social media Instagram ahead of the 2024 elections. The research results showed a shift in the political ethics of Indonesian citizens in the digital realm towards a better direction. Even though there was still a lot of conflict, disputes, commotion in the digital world in the 2024 election. Sharp discourse in the digital world in the 2024 Election, which was accompanied by data-based campaigns, was in line with the concept of worldly ethics initiated by Hannah Arendt. This concept can also be a solution to overcome the negative side of digital politics, including in the 2024 elections. Moreover, the existing dynamics of digital politics were based on non-primordial political ethics, that is, they are not accompanied by narratives of identity politics among citizens.